Dukungan Keluarga Dalam Keberhasilan Pemberian ASI Eksklusif Pada Ibu Bekerja Di Desa Sendangsari, Pajangan Bantul - Desi Ekawati; Ahtsma; Istri Bartini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The success of exclusive breastfeeding is important because it can increase a child's height growth and help prevent malnutrition in children aged 0-24 months. Sendangsari Village, Gupawarak Hamlet has a large number of breastfeeding mothers who work, so exclusive breastfeeding is not well provided for. The factors that influence the success of exclusive breastfeeding are very diverse, and one of the most influential factors is family support, especially support from husbands, parents and other family members. Family support is provided to form and increase the mother's confidence in breastfeeding and become a motivation tobreastfeed thereby increasing breast milk production. This research aims to determine the forms and efforts of family support for the success of exclusive breastfeeding for working mothers.Method: This type of research is a qualitative descriptive ethnographic design. The number of informants was 6 people consisting of two mothers-in-law, two biological mothers and two husbands. The research instrument is an interview guide using cellphones and stationery. The population of this study were working breastfeeding mothers, husbands and family members. The data analysis techniques used were data collection, data reduction, data display/data presentation, and drawing conclusions.Result: The research results found several things regarding forms of support, support efforts in storing breast milk, support for increasing breast milk production and providing information. In conclusion, family support takes the form of emotional,instrumental, appreciation or assessment and informational supportKey words: Family support, exclusive breastfeeding, working mother